Alocação de recursos em sistemas Internet das Coisas utilizando aprendizagem por reforço - Vasconcelos, Matheus Matos (2021)
This paper proposes a utilization of a reinforcement learning (RL) algorithm to control the packet transmission of multiple devices of a Cognitive Internet of Things (IoT) wireless communication system. The proposed approach consists of adopting a Markov chain to model the states of the communication system and its transitions, providing the required parameters to determine actions to the system using a Q-Learning algorithm. This paper also presents a performance evaluation of the developed algorithm in comparison to some scheduling algorithms in terms of: utility function, flow rate, buffer occupancy, packet loss rate, etc.